RADIUS PUTAR KENDARAAN DESAIN UNTUK PERANCANGAN GEOMETRIK JALAN DI INDONESIA - Greece Maria Lawalata; Faisal Rahman (Direktorat Bina Teknik Jalan dan Jembatan, 2020)
ABSTRACT Designing the width of the vehicle lane must consider the type of vehicle that passes through it. This is obtained by knowing the dimensions of the vehicle and the vehicle's wheelbase. From these two data we can find out the wheel tracks and the outer size of the vehicle body (sweeping path). This paper is intended to determine the turning radius of a design vehicle for the geometric design of the road. The design vehicles in question are the vehicles whose dimensions are mentioned in various regulations and vehicles which are the dominant results of research on the Road and Bridge Research and Development Center. The method used is a literature study of the rules and research results of the Road and Bridge Research and Development Center. Determination of the turning radius of the vehicle is done using the Autoturn software application with the assumption: flat pavement surface, the tire does not slip, the vehicle steering lock is 40o, the steering angle is 31.6o, the U-turn maneuver is 180o. The results showed that there were 17 vehicles that became design vehicles equipped with a turning radius. There are 2 vehicles that have 2 vehicles that have a turning radius of more than 12 meters. Keywords: vehicle turning radius, vehicle trail, vehicle design, vehicle dimensions, road geometric procedures.